Investigating multiple domains of household livelihood security: Insights from urban slums in Bangladesh - Akter, S; Rahman, S (Taylor and Francis (Routledge), 2016)
In this paper, we construct indices of Household Livelihood Security (HLS) domains, namely, economic, food, health, and education securities and empowerment with data from 1120 poor households in two urban settlements of Bangladesh. We then jointly identify domain-specific socio-economic determinants employing a multivariate Tobit model. A quintile analysis of domains shows high levels of inequalities amongst these poor households. The HLS domains are significantly positively correlated and a host of factors significantly influence individual HLS domain. Interventions targeted at improving education, provision of business training and building of land asset are suggested to improve livelihood security.